2013
DOI: 10.1007/s10096-013-1976-8
|View full text |Cite
|
Sign up to set email alerts
|

A rapid, low-cost quantitative diagnostic method for hepatitis C virus infection using capillary zone electrophoresis

Abstract: Hepatitis C virus (HCV)-RNA amplification is a costly procedure in terms of time and reagents. Consequently, the search for more a cost-effective specific HCV diagnostic method is of great interest. Capillary zone electrophoresis (CZE) methods that detect HCV in serum, plasma, whole blood, and ascites without the need for sample pretreatment are not currently available. Here, a CZE method was developed that detects a larger specific peak in serum and other body fluids of HCV-infected patients than that found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…These findings allowed to optimize the rapid MECK analysis of these five phages species, in whole blood and plasma samples. A similar study, with clinical relevance, was reported by Attallah et al [60] with the CZE detection and diagnostic of hepatitis C virus in less than 15 min.…”
Section: Electromigration‐based Electrokinetic Analysis Of Intact Microorganismssupporting
confidence: 81%
“…These findings allowed to optimize the rapid MECK analysis of these five phages species, in whole blood and plasma samples. A similar study, with clinical relevance, was reported by Attallah et al [60] with the CZE detection and diagnostic of hepatitis C virus in less than 15 min.…”
Section: Electromigration‐based Electrokinetic Analysis Of Intact Microorganismssupporting
confidence: 81%
“…CE detection of microorganisms can be based on the detection of cells [10][11][12][13][14][15][16][17][18], proteins [19][20][21], liposomes [22], or nucleic acids. Among them, nucleic acid detection eliminates many types of false positive and negative results, offering a more precise diagnosis.…”
Section: Diagnosing Infectious Diseases With Cementioning
confidence: 99%
“…Consequently, non‐enveloped icosahedral viruses possess a global negative surface charge at pH higher than the isoelectric point contributing to proffer them an electrophoretic mobility . Exploiting this characteristic, it has been shown that capillary zone electrophoresis (CZE), a separative analytical technique based on the difference of the electrophoretic mobility of the analytes , can be applied in the separation, detection and quantification of viral, subviral and virus‐like particles in aqueous media . However, in practice, the CZE analysis of viruses is harder than of molecules, where uncontrolled viral particles aggregation and capillary wall adsorption responsible of irreproducible results having been often encountered .…”
Section: Introductionmentioning
confidence: 99%